PERANAN PROGRAM BEASISWA UMROH MUNAQOSAH TAHFIDZ AL-QUR'AN TERHADAP PEMBENTUKAN KARAKTER RELIGIUS SISWA DI SMA NEGERI 2 LEMBANG - Nur Inayah, Sifa; Rahmat; Iswandi, Dede (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of the Umrah Scholarship Program for the Qur’an Tahfidz Munaqosah in shaping the religious character of students at SMA Negeri 2 Lembang. The research employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation. The analysis was based on Thomas Lickona’s character education theory, which includes the aspects of moral knowing, moral feeling, and moral action. The findings indicate that the program plays a positive role in developing students’ religious character. In the aspect of moral knowing, students gain an understanding of Islamic values embedded in tahfidz activities. In the aspect of moral feeling, the program fosters spiritual awareness and a deeper love for the Qur’an. Meanwhile, in the aspect of moral action, students demonstrate positive behavioral changes, including increased discipline in worship, responsibility, politeness and social concern. Therefore, the Umrah Scholarship Program for the Qur’an Tahfidz Munaqosah serves as an effective strategy for strengthening students’ religious character within the school environment.